2012
DOI: 10.1016/j.aat.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative analgesic effect of intrathecal magnesium and fentanyl added to bupivacaine in patients undergoing lower limb orthopedic surgery

Abstract: Addition of intrathecal magnesium sulfate to spinal anesthesia induced by bupivacaine significantly prolonged the onset of both sensory and motor blockade compared with fentanyl. Although magnesium failed to prolong the time to first analgesic requirement as seen with fentanyl, it reduced the total consumption of opioids in the first 12 hours postoperatively compared with the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
41
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 35 publications
9
41
1
1
Order By: Relevance
“…An inverse relationship has been demonstrated between the severity of pain with different painful medical and surgical conditions and the serum magnesium concentration [25]. Direct intrathecal administration of magnesium has been shown to prolong the action of subarachnoid anaesthesia in animal experiments [27] and in humans [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However magnesium sulphate is currently unlicensed for intrathecal use in the UK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An inverse relationship has been demonstrated between the severity of pain with different painful medical and surgical conditions and the serum magnesium concentration [25]. Direct intrathecal administration of magnesium has been shown to prolong the action of subarachnoid anaesthesia in animal experiments [27] and in humans [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However magnesium sulphate is currently unlicensed for intrathecal use in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have evaluated use of magnesium intrathecally and shown to prolong the action of subarachnoid anaesthesia [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used an opioid along with magnesium, which could have contributed to the prolongation of blockade after subarachnoid block [6][7][8][9][10][11][12][13], Magnesium alone with LA in a dose of 50 mg and maximum upto 100 mg has been used in a few studies [14][15][16][17][18][19]. Although the results of adding MgSO 4 50 mg to IT bupivacaine are conflicting, the effect of increasing the dose of additional MgSO 4 has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this procedure has only a limited duration of analgesia and causes maternal hypotension perioperatively, which may be deleterious in PIH patients. The discovery of various spinal receptors like α 2 -adrenergic, cholinergic, opioid, N-methyl-D-aspartate, gamma-aminobutyric acid (GABA), and benzodiazepine receptors triggered the usage of drugs like clonidine, neostigmine, opioids, ketamine, and midazolam for their synergistic effect with hyperbaric bupivacaine (0.5%) in prolonging the duration of analgesia (1,2). In addition, the efficacy of intrathecal amitriptyline and doxepin, which belong to different classes of drugs, have been studied in rats (3).…”
Section: Introductionmentioning
confidence: 99%